Quviasukvik. The celebration of an Inuit winter feast in the central Arctic - Frédéric Laugrand; Jarich Oosten (Journal de la Société des Américanistes)
Quviasukvik. The celebration of an Inuit winter feast in the central Arctic. In this paper we discuss the celebration of Christmas among the Inuit of Northeast Canada. Their adoption of Christianity implied a break with the past. Missionaries as well as Inuit contrasted the traditional life dominated by many ritual rules, with the new Christian life. In practice, the transition was much more complex. Many old ideas and practices did not die as easily as missionaries or Inuit assumed, but returned in a new guise. Using White and Inuit testimonies, we examine here the nature of this transition by comparing the pre-Christian Inuit winter-feasts with the celebration of Christmas after the conversion to Christianity. Many features of the pre-Christian religion returned in the Christmas celebrations but in a new context and provided with new meanings. We have considered temporal and regional variation as well as the differences between the Catholic and Anglican versions of the feast. Central topics are: gifts, food and drinks, games and sexual symbolism.